Gendist: An R package for generated probability distribution models - Bakar, S.A.A.; Nadarajah, S.; Kamarul Adzhar, Z.A.A.; Mohamed, I. (Public Library of Science, 2016)
In this paper, we introduce the R package gendist that computes the probability density function, the cumulative distribution function, the quantile function and generates random values for several generated probability distribution models including the mixture model, the composite model, the folded model, the skewed symmetric model and the arc tan model. These models are extensively used in the literature and the R functions provided here are flexible enough to accommodate various univariate distributions found in other R packages. We also show its applications in graphing, estimation, simulation and risk measurements.